Unexpectedly life-threatening meal: Contamination by Bongkrekic acid in Taiwan - Ching-Hsiang Yu; En-Chih Liao; Yu-Jang Su (Taiwanese Journal of Obstetrics & Gynecology)
Objective: Bongkrekic acid (BKA) is a life-threatening toxin linked to foodborne illnesses. Herein, we report two fatalities among 33 patients who ingested BKA in March 2024, East Taipei, Taiwan. Case Report: Our first case involved a 40-year-old female who presented with nausea, vomiting, and diarrhea after consuming wet rice noodles. On examination, refractory hypotension, jaundice, diffuse abdominal pain, high levels of liver enzymes, metabolic acidosis, coagulopathy, and acute hepatic failure were present. Dialysis, continuous venovenous hemofiltration, and plasma exchange were performed; however, the patient experienced liver failure and died of multi-organ failure, severe sepsis, and coagulopathy on day 39. The second case, a 39-year-old man, was found unconscious and experiencing cardiac arrest. He eventually died after 30 min of cardiopulmonary resuscitation following admission to the intensive care unit. Conclusion: Strengthening food safety regulations by enhancing inspection of food production, storage, and preparation facilities should be implemented to prevent BKA poisoning-related fatalities.